Combining ability analysis for grain and fodder traits in sorghum (Sorghum bicolor (L.) Moench) - Khana, Rumana; Ranwah, Balu Ram; Sharma, Vijay; Khandagale, Subodh (Bangladesh Journal of Botany, 2020)
Over the environment, on the basis of days to flowering and suitability for dual purpose analysis was carried out of 100 genotypes including 75 F1s with 20 parents and 5 checks. Data were collected for grain yield, dry fodder yield, protein content in grain, protein content in fodder, TSS and juiciness. Variations between lines, testers and line × tester was significant for all characters. As both grain and dry fodder yield are important dual-purpose attributes, lines ICSA 202, ICSA 349 and ICSA 357 and ICSA 481 were found to be good general combiners for both grain and dry fodder yield. Two crosses viz., ICSA 29002 × SU 1565 and ICSA 356 × SU 1570 exhibited significant SCA effects in all the four environments whereas hybrids ICSA 552 × SU 1561, ICSA 202 × SU 1570, ICSA 349 × SU 1561, ICSA 208 × SU 1561, ICSA 474 × SU 1561 and ICSA 357 × SU 1565 showed good SCA effects in normal spacing (E1 and E3) and ICSA 481 × SU 1561 and ICSA 399 × SU 1557 in wider spacing (E2 and E4) for both grain and dry fodder yield. These lines and crosses also expressed positive significant GCA and SCA effects for majority of the remaining fodder quality traits.